Identification of pork flavour precursors from enzyme-treated lard using Maillard model system assessed by GC–MS and partial least squares regression. (February 2017) - Song, Shiqing; Tang, Qi; Fan, Li; Xu, Xiaodong; Song, Ze; Hayat, Khizar; Feng, Tao; Wang, Yifei
Abstract: Lipase was used to hydrolyse the lard, and four pork flavours (PFs) were prepared through Maillard reaction using different enzyme-treated lards. Volatile compounds and free fatty acids of lard, and volatile compounds of PFs were analysed by GC–MS. The results showed that the total free fatty acids (FFAs) were 89.40%, 85.80% and 89.92% lower in lard control compared with three different enzyme-treated lards (S1, S2 and S3), respectively. Analysis of volatiles of PFs indicated that the effect of lard with moderate lipase treatment on Maillard reaction was more prominent than that of others. The results of descriptive sensory analysis confirmed that PF3 from S3 had the strongest porky, meaty and odour-tenacity. The relationship between FFAs in lard and volatile compounds and sensory attributes of the PFs showed that 9c-C18:1 oleic acid, 9t-C18:1 elaidic acid, 10c-C17:1 heptadecenoic acid, 9c, 12c-C18:2 linoleic, C18:0 stearic and 9c-C16:1 palmitoleic might be pork flavour precursors which were present at highest concentrations in lipase MER "Amano" pretreated lard. Highlights: Enzymed lard is useful in accentuating typical meat flavour in model system. Lipase hydrolysis treatment is a desirable method for preparing flavour precursors. Six free fatty acids were identified as potential pork flavour precursors.